The history of cacao and its diseases in the Americas - Díaz-Valderrama J.R. (2020)
Cacao is a commodity crop from the tropics cultivated by about 6 million smallholder farmers. The tree, Theobroma cacao, originated in the Upper Amazon where it was domesticated ca. 5450 to 5300 B.P. From this center of origin, cacao was dispersed and cultivated in Mesoamerica as early as 3800 to 3000 B.P. After the European conquest of the Americas (the 1500s), cacao cultivation intensified in several loci, primarily Mesoamerica, Trinidad, Venezuela, and Ecuador. It was during the colonial period that cacao diseases began emerging as threats to production. One early example is the collapse of the cacao industry in Trinidad in the 1720s, attributed to an unknown disease referred to as the “blast”. Trinidad would resurface as a production center due to the discovery of the Trinitario genetic group, which is still widely used in breeding programs around the world. However, a resurgence of diseases like frosty pod rot during the republican period (the late 1800s and early 1900s) had profound impacts on other centers of Latin American production, especially in Venezuela and Ecuador, shifting the focus of cacao production southward, to Bahia, Brazil. Production in Bahia was, in turn, dramatically curtailed by the introduction of witches’ broom disease in the late 1980s. Today, most of the world’s cacao production occurs in West Africa and parts of Asia, where the primary Latin American diseases have not yet spread. In this review, we discuss the history of cacao cultivation in the Americas and how that history has been shaped by the emergence of diseases. © 2020 The American Phytopathological Society.